Electrical characterization of 2D materials-based field-effect transistors. (19th November 2020) - Mitta, Sekhar Babu; Choi, Min Sup; Nipane, Ankur; Ali, Fida; Kim, Changsik; Teherani, James T; Hone, James; Yoo, Won Jong
Abstract: Two-dimensional (2D) materials hold great promise for future nanoelectronics as conventional semiconductor technologies face serious limitations in performance and power dissipation for future technology nodes. The atomic thinness of 2D materials enables highly scaled field-effect transistors (FETs) with reduced short-channel effects while maintaining high carrier mobility, essential for high-performance, low-voltage device operations. The richness of their electronic band structure opens up the possibility of using these materials in novel electronic and optoelectronic devices. These applications are strongly dependent on the electrical properties of 2D materials-based FETs. Thus, accurate characterization of important properties such as conductivity, carrier density, mobility, contact resistance, interface trap density, etc is vital for progress in the field. However, electrical characterization methods for 2D devices, particularly FET-related measurement techniques, must be revisited since conventional characterization methods for bulk semiconductor materials often fail in the limit of ultrathin 2D materials. In this paper, we review the common electrical characterization techniques for 2D FETs and the related issues arising from adapting the techniques for use on 2D materials.